Continuous One-Counter Automata - Blondin, Michael; Leys, Tim; Mazowiecki, Filip; Offtermatt, Philip; Perez, Guillermo A. (Proceedings of the 36th Annual ACM/IEEE Symposium on Logic in Computer Science, 2021)
We study the reachability problem for continuous one-counter automata, COCA for short. In such automata, transitions are guarded by upper and lower bound tests against the counter value. Additionally, the counter updates associated with taking transitions can be (non-deterministically) scaled down by a nonzero factor between zero and one. Our three main results are as follows: (1) We prove that the reachability problem for COCA with global upper and lower bound tests is in NC2; (2) that, in general, the problem is decidable in polynomial time; and (3) that it is decidable in the polynomial hierarchy for COCA with parametric counter updates and bound tests.